Aesculus hippocastanum L. Extract Does Not Induce Fibroblast to Myofibroblast Conversion but Increases Extracellular Matrix Production In Vitro Leading to Increased Wound Tensile Strength in Rats - Kováč, Ivan; Melegová, Nikola; Čoma, Matúš; Takáč, Peter; Kováčová, Katarína; Hollý, Martin; Ďurkáč, Ján; Urban, Lukáš; Gurbáľová, Miriam; Švajdlenka, Emil; Mojžišová, Gabriela; Zajíček, Robert; et al. (Molecules, 2020)
The ability of horse chestnut extract (HCE) to induce contraction force in fibroblasts, a process with remarkable significance in skin repair, motivated us to evaluate its wound healing potential in a series of experiments. In the in vitro study of the ability of human dermal fibroblasts to form myofibroblast-like cells was evaluated at the protein level (Western blot and immunofluorescence). The in vivo study was conducted on male Sprague-Dawley rats with inflicted wounds (one open circular and one sutured incision) on their backs. Rats were topically treated with two tested HCE concentrations (0.1% and 1%) or sterile water. The control group remained untreated. The incisions were processed for wound tensile strength (TS) measurement whereas the open wounds were subjected to histological examination. On the in vitro level the HCE extract induced fibronectin-rich extracellular matrix formation, but did not induced α-smooth muscle actin (SMA) expression in dermal fibroblasts. The animal study revealed that HCE increased wound TS and improved collagen organization. In conclusion, the direct comparison of both basic wound models demonstrated that the healing was significantly increased following HCE, thus this extract may be found useful to improve healing of acute wounds. Nevertheless, the use of an experimental rat model warrants a direct extrapolation to the human clinical situation.
Keywords: Animals; Regeneration; rostlinné extrakty; Wound Healing; vysokoúčinná kapalinová chromatografie; Molecular Structure; Aesculus; Tensile Strength; extracelulární matrix; regenerace; molekulární struktura; Chromatography, High Pressure Liquid; myofibroblasty; Myofibroblasts; hojení ran; Plant Extracts; krysa rodu Rattus; Extracellular Matrix; zvířata; Rats; pevnost v tahu